Nicotine Self-Administration Induces CB1-Dependent LTP in the Bed Nucleus of the Stria Terminalis - Reisiger, Anne-Ruth (J Neurosci, 2014)
Nicotine addiction is characterized by repetitive drug taking and drug seeking, both tightly controlled by cannabinoid CB1 receptors. The responsiveness of neurons of the bed nucleus of the stria terminalis (BNST) to infralimbic cortex (ILCx) excitatory inputs is increased in rats with active, but not passive, nicotine taking. Therefore, we hypothesize that acquisition of the learned association between nicotine infusion and a paired cue light permits the strengthening of the ILCx–BNST synapses after ILCx tetanic stimulation. We exposed rats to intravenous nicotine self-administration for 2 months. Using a combination of in vivo protocols (electrical stimulations, extracellular recordings, and pharmacological manipulations), we characterized the effects of 10 Hz stimulation of the ILCx on BNST excitatory responses, under different conditions of exposure to nicotine. In addition, we tested whether the effects of the stimulation were CB1 receptor-dependent. The results show that nicotine self-administration supports the induction of evoked spike potentiation in the BNST in response to 10 Hz stimulation of ILCx afferents. Although not altered by nicotine abstinence, this cellular adaptation was blocked by CB1 receptor antagonism. Moreover, blockade of BNST CB1 receptors prevented increases in time-out responding subsequent to ILCx stimulation and decreased cue-induced reinstatement. Thus, the synaptic potentiation within the BNST in response to ILCx stimulation seems to contribute to the cue-elicited responding associated with nicotine self-administration and is tightly controlled by CB1 receptors.